Detection of Embedded Low-level Radioactive Shrapnel after the Explosion of a Radiological Dispersal Device in Radiological Emergency Imaging. Issue 1 (July 2020) - Majewski, Matthäus; Nestler, Kai; Veit, Daniel A.; Diekmeyer, Birte; Waldeck, Stephan; Port, Matthias; Becker, Benjamin V.
Abstract : Abstract: Concern about the threat of a terrorist attack with a Radiological Dispersal Device has increased considerably over the last few years, and this comes along with an immense challenge, especially regarding medical treatment of combined injuries with incorporated radioactive fragments. In such scenarios, the identification and surgical exploration of radioactive fragments is a major issue to prevent further radiation-induced effects like wound healing disorders, onset of acute radiation syndrome, and as a late-effect cancer. However, in a usual emergency setting, it is unclear how this task can be achieved. Within this study, we evaluated the feasibility of different radiological methods to identify and locate an incorporated radioactive fragment. We placed two different 137 Cs sources and several non-radioactive fragments representing sham control samples within a human spine phantom. Standard emergency imaging procedures were performed, including plane radiography and different CT scans (64 row, 384 row dual energy, 320 row without iterative metal artifact reduction), respectively. Eight radiologists were blinded toward the results and asked to identify the radioactive fragments within the provided images. For both sources, correct identification was rather low (15.63%). Furthermore, none of the questioned radiologists (N = 0) stated that they were able to identify the radioactive shrapnel distinctly. Positive predictive value was accordingly low (15.63%). Most participants recommended a scintigraphy-based technique for identification (26.67%) rather than radiographic procedures (6.67%). Identification and location of incorporated small radioactive fragments with low energies by standard radiological procedures prior to surgical exploration is not promising. Nevertheless, procedures that can achieve this aim are needed direly in the case of a terrorist attack with a radiological dispersal device and should be available in an emergency department.